Banana-derived excipients: drug release, performance, and stability - Fauzi, Muh Fajar (Pharmacy Reports, 2025)
Banana-derived excipients have garnered increasing attention due to their potential as natural, sustainable alternatives in pharmaceutical formulations. This study systematically reviewed the effectiveness and compatibility of banana-based excipients compared to conventional synthetic and natural counterparts. A comprehensive literature review was conducted following the PICOS framework, covering studies published between 2013 and 2024. Data extraction focused on physicochemical characterization, functional performance, and drug release properties of banana-derived excipients across various dosage forms. The results indicate that banana starch and crude banana powder exhibit promising binding, disintegrant, and mucoadhesive properties. Their performance in pharmaceutical formulations was comparable to widely used excipients such as maize starch, polyvinylpyrrolidone (PVP), and microcrystalline cellulose. Notably, banana-derived excipients demonstrated sustained-release effects and potential bioavailability enhancement. However, a lack of standardization in processing methods and limited stability data highlight the need for further research to ensure reproducibility and regulatory compliance. Despite their advantages, challenges remain in optimizing formulations and understanding long-term interactions with drug compounds. Future studies should focus on in vivo validation and stability assessments to enhance the adoption of banana-based excipients in pharmaceutical applications. This research contributes to the growing field of sustainable pharmaceutical development by advocating for the integration of environmentally friendly excipients into modern drug formulations.